Diversity of MIMO Linear Precoding - Mehana, Ahmed Hesham; Nosratinia, Aria (IEEE transactions on information theory, 2014)
This paper studies multiple-input multiple-output linear precoding in the high-signal-to-noise-ratio regime under flat fading. The diversity at all fixed rates is analyzed for a number of linear precoders. The diversity-multiplexing tradeoffs (DMTs) are also obtained, discovering that for many linear precoders the DMT gives no direct insight into the intricate behavior of fixed-rate diversity. The zero-forcing (ZF), regularized ZF, matched filtering, and Wiener filtering precoders are analyzed. It is shown that regularized ZF (RZF) or matched filter (MF) suffers from error floors for all positive multiplexing gains. However, in the fixed rate regime, RZF and MF precoding achieve full diversity for spectral efficiencies up to a certain threshold and zero diversity at rates above it. When the regularization parameter in the RZF is optimized in the minimum mean square error sense, the structure is known as the Wiener precoder, which in the fixed-rate regime is shown to have diversity that depends not only on the number of antennas, but also on the spectral efficiency. The diversity in the presence of both precoding and equalization is also analyzed.